2017
DOI: 10.17221/46/2016-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Induction of accessory corpus luteum by gonadorelin in relation to the time of treatment and the follicle size in inseminated cows

Abstract: Doležel R., Chambert C., Musilová D., Čech S., Páleník T. (2017): Induction of accessory corpus luteum by gonadorelin in relation to the time of treatment and the follicle size in inseminated cows. Czech J. Anim. Sci., 62,[195][196][197][198][199][200] This study evaluated the occurrence of two corpora lutea (CL) and the pregnancy rate in cows treated with gonadorelin on days 5, 6 or 7 after insemination in relation to the day of treatment and the size of the largest follicle on the ovaries at the time of trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
1
0
Order By: Relevance
“…In our previous study, we confirmed that administering GnRH between 7-14 days after artificial insemination (AI) can increase the number of aCL and improve reproductive performance in repeat-breeder dairy cows [1]. According to the results of Doležel et al, [17], inducing aCL through gonadorelin administration was found to be more efficient in cows treated on day 5 following insemination, as compared to cows treated on days 6 or 7. A study conducted by Cunha et al [6] Disclaimer/Publisher's Note: The statements, opinions, and data contained in all publications are solely those of the individual author(s) and contributor(s) and not of MDPI and/or the editor(s).…”
Section: Introductionmentioning
confidence: 61%
“…In our previous study, we confirmed that administering GnRH between 7-14 days after artificial insemination (AI) can increase the number of aCL and improve reproductive performance in repeat-breeder dairy cows [1]. According to the results of Doležel et al, [17], inducing aCL through gonadorelin administration was found to be more efficient in cows treated on day 5 following insemination, as compared to cows treated on days 6 or 7. A study conducted by Cunha et al [6] Disclaimer/Publisher's Note: The statements, opinions, and data contained in all publications are solely those of the individual author(s) and contributor(s) and not of MDPI and/or the editor(s).…”
Section: Introductionmentioning
confidence: 61%
“…Few studies have been conducted on changes in the corpus luteum tissue during pregnancy, and most suggest that 20α-HSD-mediated apoptosis during early pregnancy may indicate abortion (Naidansuren et al 2012). However, the corpus luteum undergoes active tissue reorganisation during pregnancy and the functional activity of the corpus luteum changes accordingly (Kim et al Supplement of 20α-HSD protein 0.5 μg/ml 1 μg/ml 1.5 μg/ml 0.5 1 1.5 (μg/l) 2014; Dolezel et al 2017). The process of reconstitution of the corpus luteum is accomplished by transforming growth factor-beta (TGF-β) signalling, T cell receptor signalling/Ilyushin-2 (IL2) signalling, which is a luteinising enzyme, and the activity of matrix metalloproteinases by extracellular matrix collagen (ADAMTS1) affects the extracellular matrix, resulting in the overall degeneration of the corpus luteum tissue (Kim et al 2014;.…”
Section: Discussionmentioning
confidence: 99%